IMPROVING ORGANIZATIONAL WORK PROCESS OF LAND REGISTRATION BASED ON 3D CADASTRE AND CADASTRE 2014 CONCEPTS (Case Study Apartment Unit Registration) - M Arif Suhattanto (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
The need for land always increases but the area of land never increases. This makes people to use the landeffectively. The use of traditional cadastre; the use of 2 dimensional cadastral concept, is no longer able to fulfill the completecadastral needs. Having experiments on applying the 2 dimensional land registration, knowledge on 2014 cadastral conceptsand 3 dimensional cadastral concepts, the development of the ongoing organization’s work process is badly required. The paperis aimed at explaining how to design the process of land registration in applying the 3 D cadastral and 2014 cadastral conceptsusing a modeling process. The result of the process is the new diagram showing the change of the organization; both inside andoutside. However, due to the complexity of the 3 D cadastral concept, the discussion is limited to the apartment units inIndonesia.Keywords: 3D cadastre, 2014 cadastre, modeling.